ERS/ELS/ACCP 2013 international consensus conference nomenclature on inducible laryngeal obstructions - Christensen, Pernille M.; Heimdal, John-Helge; Christopher, Kent L.; Bucca, Caterina; Cantarella, Giovanna; Friedrich, Gerhard; Halvorsen, Thomas; Herth, Felix; Jung, Harald; Morris, Michael J.; Remacle, Marc; Rasmussen, Niels; et al. (European respiratory review, 2015)
Individuals reporting episodes of breathing problems caused by re-occurring variable airflow obstructions in the larynx have been described in an increasing number of publications, with more than 40 different terms being used without consensus on definitions. This lack of an international consensus on nomenclature is a serious obstacle for the development of the area, as knowledge from different centres cannot be matched, pooled or readily utilised by others. Thus, an international Task Force has been created, led by the European Respiratory Society/European Laryngological Society/American College of Chest Physicians. This review describes the methods used to reach an international consensus on the subject and the resulting nomenclature, the 2013 international consensus conference nomenclature. - Tweetable abstract ERSpublications - click to tweetThe condition leading to episodes of feeling like you cannot breathe now has a name: inducible laryngeal obstructions http://ow.ly/OMaNl